2016
DOI: 10.17547/kjsr.2016.24.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Personality and Coping Behavior on Clinical Practice Stress among One College Nursing Students

Abstract: The purpose of this descriptive study was to investigate the effects of personality and coping behavior on clinical practice stress in nursing students which was experienced at clinical practice. The data were collected using questionnaire from the convenience sample of 88 nursing students. The data were collected from May 21 to 31, 2016. Data were analyzed with independent t-test, one way ANOVA, Pearson correlation coefficients, and multiple regression by using SPSS version 23.0. The mean score for clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…All the variables presented in the study were positively correlated with the students' clinical clerkship satisfaction; while, neurosis (of personality dimensions) was negatively correlated. Findings are in concert with previous studies [8,11,39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All the variables presented in the study were positively correlated with the students' clinical clerkship satisfaction; while, neurosis (of personality dimensions) was negatively correlated. Findings are in concert with previous studies [8,11,39].…”
Section: Discussionsupporting
confidence: 91%
“…Personality characteristics are predictor of burnout and program completion in intern nursing students [10]. Furthermore, previous studies showed clinical performance of students is associated with their personality characteristics [11,12]. Herein, for evaluating personality dimensions of student nurses, Costa and McCrae's "Big-Five-factor" theory of personality was employed.…”
Section: Personality Dimensionsmentioning
confidence: 99%
“…Personality characteristics are predictors of burnout and program completion among intern nursing students [10]. Furthermore, previous studies have showed clinical performance of students is associated with their personality characteristics [11,12]. Herein, to investigate personality dimensions of student nurses, Costa and McCrae's "Big-Five-factor" theory of personality was employed.…”
Section: Personality Dimensionsmentioning
confidence: 99%
“…Furthermore, previous studies have showed clinical performance of students is associated with their personality characteristics [11,12]. Herein, to investigate personality dimensions of student nurses, Costa and McCrae's "Big-Five-factor" theory of personality was employed.…”
Section: Personality Dimensionsmentioning
confidence: 99%
“…To succeed in the nursing profession, personality type is very important.Some people with certain personality traits perform better as a nurse [9]. For example, students who are extrovert have a better adaptation to nursing and higher clinical performance [8,11]. Responsibility and openness are also associated with higher job performance and lower burnout [14].…”
Section: Research Frameworkmentioning
confidence: 99%